Simulación de procesos industriales mediante variadores de frecuencia y el protocolo de comunicación MODBUS-RTU - Guadalupe Lachi, David Israel (2021)
The current research project has described the simulation of industrial processes, the dosing tanks, conveyor belts, and the application of a panel with industrial characteristics. It is coupled with Modbus RTU communication protocol for the simulation, control, and monitoring of the industrial control laboratory's electric parameters. The design, connection, wiring, conditioning, and configuration of the devices will be part of the industrial network. This industrial network consists of four phases. The first is the design and construction of the panel with industrial characteristics installed in a section of the laboratory. The second phase is the communication of serial devices where the field devices are actuated through a PLC with data organization Master/Slave with the Modbus RTU communication protocol. A star topology will determine, it will integrate a configuration with hexadecimal data for writing or Reading, as appropriate. In the third phase, the simulation of tank design and conveyor belts in the FACTORY I/O software represents natural processes. Finally, visualization, control, and monitoring of electrical parameters on the HMI screen. The research process aims to illustrate better automation processes developed in the industry and strengthen the learning process in Modbus networks, thus encouraging the Industrial Control and Automation department's study.